Knowledge and practices of midwives regarding the utilization of cardiotocography in labour units at Mokopane and Voortrekker Hospitals, Waterberg District in Limpopo Province - Mazwi, Ruth Raesetja (My University, 2020)
The aim of the study is to determine the knowledge and practices of midwives regarding the utilization of cardiotocography in labour units, at Hospital A and Hospital B, Waterberg District in Limpopo Province. Further, the objective of the study is to explore and describe the knowledge and practices of midwives regarding the utilization of cardiotocography in labour units and to develop strategies to enhance midwifery practices and knowledge regarding the utilization of cardiotocography in the labour units of Hospital A and Hospital B. The research question is:” What is the knowledge and practices of midwives regarding the utilization of cardiotocography in the labour units of Hospital A and Hospital B?” The Donabedian Model has been used as a theoretical framework. A qualitative exploratory, descriptive and contextual research design has been used in this study. Purposive sampling was used to sample eighteen (18) participants from Hospital A and Hospital B. Data was collected using semi-structured interviews. Tesch’s eight steps of qualitative data analysis were followed and two themes and ten sub-themes emerged. The study found that there were several challenges encountered by participants such as a shortage of material and human resources and lack of continuous training which has a negative impact on the provision of midwifery care. The study recommends that the Department of Health should appointment new skilled midwives as there is shortage of staff, to improve service delivery. It should ensure that there is a guaranteed supply and availability of equipment, such as CTG. The nursing administration should ensure that there is adequate training for midwives. This includes in-service training, workshops and a post basic advanced midwifery course.
Thesis (M.A. (Nursing Science)) -- University of Limpopo, 2020
Keywords: Knowledge; Practice; Utilization; CTG; Midwives; Fetal heart rate monitoring; Fetal monitoring; Midwifery; Midwives